1901 Mich. Pub. Acts 158 - (:unkn) unknown (My University, 1901)
Local Acts, tit. 7, no. 344, § 24, pt. 49: To prohibit and punish the use of toys pistols, air guns, sling shots and other dangerous toys, implements or weapons within said city.
Keywords: DISCHARGE